Synthesis, Physico-Chemical Characterization, Antibacterial and Antifungal Activities Studies of a New Schiff Base Ligand and its Transition Metal Complexes - Sahal, Hakan; Canpolat, Erdal; Kaya, Mehmet; Kara, Nazan (Chem Soc Pakistan, 2015)
The complexes of Co(II), Cu(II) and Zn(II) with the Schiff base 2-[(E)-{[4-(4-aminophenoxy)phenyl] imino}methyl]-6-ethoxyphenol (LH) have been synthesized and their structure have been elucidated on the basis of elemental analyses, IR, H-1- and C-13-NMR spectra, electronic spectra, magnetic susceptibility measurements and thermogravimetric analyses (TGA). Mononuclear complexes with a metal: ligand ratio of 1:1 have been prepared with Co+2 and Zn+2 salts, whereas the copper(II) complex is dinuclear which have a metal: ligand ratio of 2:1. According to the results, it is suggested that the ligand is coordinated to each metal atom by the phenolic oxygen and the azomethine nitrogen atoms. The synthesized compounds were tested for antimicrobial activity against in vitro antibacterial (Bacillus subtilis, Staphylococcus aureus, Escherichia coli and Salmonella typhimurium) and antifungal activities (Candida globrata and Candida tropicalis) by the minimum inhibitory concentration (MIC) method. All of the selected compounds showed weak antimicrobial activity against test microorganisms (256-1024 mu g/mL).
Keywords: Schiff base; Transition metal complexes; Antimicrobial activity; 4,4-diaminodiphenylether